تأثير الأصل الوسيط في نمو وإنتاج أشجار الحمضيات صنف (فالنسيا) - سلمان يحيى; ديب علي; الراعي جنان (Latakia University Journal -Biological Sciences Series, 2017)
أجريت الدراسة في قرية فديو(محافظة اللاذقية) خلال موسم2015-2014 على أشجارحمضيات من الصنف فالنسيا مطعمة على الأصل (الزفير) وعلى أشجار حمضيات من الصنف نفسه مطعمة على كل من الأصلين الوسيطيين(مندلينا-ساتزوما) الناميين على الأصل الجذري( الزفير) بهدف دراسة تأثير الأصل الوسيط في قوة نمو وانتاج وجودة ثمار الصنف المطعمة عليه وأظهرت النتائج الآتي : 1-الأثر الايجابي لمعاملة الوسيط مندلينا في وزن وحجم الثمرة حيث أعطت أعلى قيمة لمتوسط وزن الثمرة بواقع(234.40غ) وأعلى قيمة لها في متوسط حجمها (255.70سم3) متفوقة بفروق معنوية على معاملتي الشاهد(161.20غ،182.20سم3) والوسيط ساتزوما (169.20غ و171.40 سم3). 2-تفوق معاملة الوسيط مندلينا بفروق معنوية في متوسط وزن العصير(124.7oغ)وحجمه(128.08سم3) على معاملتي الشاهد(93.80 غ ،90.56سم3) والوسيط ساتزوما(83.10 غ،80.17 سم3). 3-تفوق معاملة الوسيط مندلينا بفروق معنوية على معاملتي الوسيط ساتسوما والشاهد في محتوى الثمار من فيتامين C(43.49 ملغ/100مل عصير )وفي معامل النضج (9.38). 4-تفوق معاملتي الوسيطين مندلينا والساتزوما على معاملة الشاهد بفروق معنوية في نسبة المواد الصلبة الذائبة حيث بلغت في كلتا معاملتي الوسيطين (10 %) في حين بلغت (8.5 %) في معاملة الشاهد. This research was conducted in Fidio village of Lattakia city during the period (2014-2015)on citrus trees of Valancia variety like a scion on the(Citrus aurantium) rootstock & on citrus trees of the same variety like a scion on each of the two interstocks (Mandalina and Satsuma) which grows on the rootstock ( Citrus aurantium). Aims of studying the interstock on growing energy, producing & improvement of scioned fruit variety. Results shows: 1-the positive effect for treatment Mandalina interstock on fruit volume and weigh, whereas the highest average of fruit weigh in dealing with Mandalina interstock was (234.40g) and the highest kotabunga average of the fruit volume(255,70)c.m3 winning by this the treatment ofwitness(182.2)c.m3-(161.2)g)&Satsuma(171.4c.m3-169.2g). 2-The interstock mandalina increased significantly in juice weigh average (124,70g) volume(128.08)c.m3 on the two control treatment (93,80g-90,56c.m3)&the interstock Satsuma(83,10g-80,17c.m3). 3-Mandalina interstock treatment was the winner on the two ones of Satsuma and the control into fruit content of vita ``C``juice(43,49mlg \100ml) and (T.S.S.%/TA%) (9,38). 4-the winning of Mandalina and Satsuma two ones and that exists in total soluble solid one,whereas the two interstockdeals were(10%) but (8,5%) in the witness deal.